ATP8B1: A prognostic prostate cancer biomarker identified via genetic analysis. Issue 6 (15th February 2023) - Chen, Lih‐Chyang; Huang, Shu‐Pin; Shih, Chieh‐Tien; Li, Chia‐Yang; Chen, Yei‐Tsung; Huang, Chao‐Yuan; Yu, Chia‐Cheng; Lin, Victor C.; Lee, Cheng‐Hsueh; Geng, Jiun‐Hung; Bao, Bo‐Ying
Abstract: Background: Controlling the asymmetric distribution of phospholipids across biological membranes plays a pivotal role in the life cycle of cells; one of the most important contributors that maintain this lipid asymmetry are phospholipid‐transporting adenosine triphosphatases (ATPases). Although sufficient information regarding their association with cancer exists, there is limited evidence linking the genetic variants of phospholipid‐transporting ATPase family genes to prostate cancer in humans. Methods: In this study, we investigated the association of 222 haplotype‐tagging single‐nucleotide polymorphisms (SNPs) in eight phospholipid‐transporting ATPase genes with cancer‐specific survival (CSS) and overall survival (OS) of 630 patients treated with androgen‐deprivation therapy (ADT) for prostate cancer. Results: After multivariate Cox regression analysis and multiple testing correction, we found that ATP8B1 rs7239484 was remarkably associated with CSS and OS after ADT. A pooled analysis of multiple independent gene‐expression datasets demonstrated that ATP8B1 was under‐expressed in tumor tissues and that a higher ATP8B1 expression was associated with a better patient prognosis. Moreover, we established highly invasive sublines using two human prostate cancer cell lines to mimic cancer progression traits in vitro. The expression of ATP8B1 was consistently downregulated in both highly invasive sublines. Conclusion: Our study indicates that rs7239484 is a prognostic factor for patients treated with ADT and that ATP8B1 can potentially attenuate prostate cancer progression.